Experimental infection of Capybaras (Hydrochoerus hydrochaeris) with an Amblyomma sculptum-derived strain of Rickettsia rickettsia - Hernandez, Alejandro Ramirez (2019)
Brazilian Spotted Fever (BSF) is recognized as the most lethal tick-borne disease in Brazil and other countries in the western hemisphere. Rickettsia rickettsii is its etiological agent, and in its natural history, ticks and mammals perform an essential epidemiologic role. In southeastern Brazil, Amblyomma sculptum is the main incriminated vector and capybaras have been recognized as amplifier hosts. Previous studies have comproved that capybaras are susceptible to infection with R. rickettsii and that develop a rickettsemia of sufficient length to infect naïve A. sculptum ticks. These studies used for infection a strain of R. rickettsii isolated from Amblyomma aureolatum ticks (strain Taiaçu) without performing subsequent infection challenges in immune animals. Herein, we present the results of an experimental study infecting capybaras with a R. rickettsii -strain isolated from A. sculptum (strain Itu) identifying clinical, haematological and pathological features, rickettsemic period and subsequent transmission of R. rickettsii to susceptible A. sculptum tick populations with a sequential analysis of their vectorial competence; also, we performed subsequent infections to evaluate the mentioned variables in immune or convalescent animals. Five capybaras, from two non-endemic regions in São Paulo state, were infected with R. rickettsii (strain Itu) through tick infestations with infected A. sculptum adults. Rectal temperature and clinical signs were registered during a 30-day following period and skin and blood samples collected, each two days, for guinea pig inoculation, DNA extraction, haematology and immunofluorescence antibody test (IFA). Also, capybaras were infested with non-infected A. sculptum ticks (nymphs and adults) in two feeding chambers (one to feed with infected adults and another to feed separated from infected adults), which were further collected, incubated and posteriorly used for infestation of susceptible rabbits and DNA extraction. These procedures were repeated during subsequent capybara infections. During primoinfection, four out of five capybaras presented clinical signs and two died, showing vascular gross lesions at necropsy. Based on guinea pig inoculation, rickettsemia was present in all capybaras with a mean duration of 9.2 days (range: 6-12 days). Rickettsia DNA was amplified in blood and skin samples from capybaras and some hematologic variables (PCV, and leucocyte count) were altered during infection. All individuals presented serological responses and maintain antibody titres during the following period (307-555 days) and, in convalescent capybaras, antibodies were detected before each subsequent infection. In those animals, no clinical signs nor rickettsemia were detected after each infection challenge. Samples of ticks collected during primoinfection of all capybaras amplified Rickettsia DNA with infectious rates of 4.6-30.0% and 5.0-100.0% in molted nymphs and adults, respectively. Also, after infestations with these ticks, rabbits presented clinical signs and serologic reactivity. By contrast, ticks collected during subsequent capybara infections did not amplify Rickettsia DNA and rabbits infested with them did not exhibited clinical signs nor antibody response. Notably, a batch of ticks collected from capybara 5, during the second infection, that fed adjacent with infected adults, amplified Rickettsia DNA, suggesting a probable R. rickettsii non-systemic horizontal transmission. In conclusion, in the present study it was corroborated capybara susceptibility to infection with R. rickettsii (strain Itu) and similar infection variables when comparing with strain Taiaçu. However, new clinical and tick transmission patterns were registered in first- infected and immune animals.